STRATEGY TO DEVELOP ENTREPRENEURIAL SPIRIT IN THE DIGITAL ERA IN ULU LAPAO-PAO, WOLO DISTRICT, KOLAKA - Syahrir, Sasmita Nabila; Agustina, Niar; Nurhaisyah, Nurhaisyah; Yuliana, Nopi; Tamriany, Novita; Rahayu, Nur Ica; Selviranda, Selviranda; Syabainul, Rengka; Muliana, Rika; Alghazali, Muhardi; Rijal, Muh.; Aldi, Aldi; Hamid, Fildzah Salsabila (Yayasan Education and Social Center, 2025)
Community Service is a real medium in bridging universities with the community in facing various social problems and needs, because universities are required not only to be centers for the development of science but also to be able to practice that knowledge for the benefit of society. Community service in carrying out socialization activities to the community in Ulu Lapao-Pao village, which is related to increasing entrepreneurial spirit in the digital era, aims to foster an entrepreneurial spirit by utilizing technology in its business activities. Based on the observations at the PKM Location, namely Ulu Lapao-Pao village, some problems are a priority in this PKM, namely the lack of community knowledge regarding how to utilize social media in entrepreneurship in the digital era. The implementation of this service uses a socialization method consisting of three stages: observation, socialization, and evaluation. The implementation of community service activities aimed at improving the knowledge and skills of the Ulu Lapao-Pao village community in entrepreneurship in the digital era can be said to have achieved success as indicated by the desire to become entrepreneurs in the digital era because their knowledge and skills in using technology as a commercial marketing tool have also developed by utilizing social media as a place for entrepreneurship in the digital era.